(untitled) (Internet of Things and Edge Computing Journal, 2023)
In today’s international retail industry, competition is fierce. Customers are not only looking for a competent retailer but for a reliable buying experience. Delays in order delivery are an indicator of the retail business’s inadequacy. Efficient order management on the back end is a critical part of swift order delivery. A good order management system will keep companies at the top of this competition. AI can assist in the efficient running of these systems. Small and medium-sized businesses usually have difficulties with their order management systems. AI is a great fit for refining business operations and can significantly enhance personnel productivity by automating simple tasks like matching and management. The aim of this study is to discuss the various aspects of potential AI-based systems in retail and identify what could be used in the creation of an effective order management system. This highlights the ability of AI to improve operating systems for retailers. There are numerous logistics-related activities, and AI has been proven to be very efficient in supply chain and production flow. Optimization of warehouse management, transportation, and container management, as well as other similar activities, is an area of interest for AI researchers. This paper may only cover the AI process and identify the different types of AI that relate to retail and distinguish AI from other operations.